CHILD DEVELOPMENT IN CHILDREN WITH MALNUTRITION - Rosmita Nuzuliana; Ellyda Rizki Wijhati (Poltekkes Kemenkes Bengkulu, 2022)
Problems that often occur in malnutrition in toddlers are susceptibility to disease and delays in their development. The purpose of this study was to observe the development of children under five with malnutrition. This study uses a case study description method with multiple cases. The cases taken were multiple cases with purposive sampling, with a total of 9 children under five as subjects. Data were collected through interviews, anthropometric measurements, developmental screening, and a healthy home assessment. We use descriptive analysis and pattern-matching analysis. We have a Result that seven toddlers experiencing suspected in delay development. Characteristics of the parents of 9 subjects are the subject has complete parents and living at the same home. Mothers as domestic workers. the Majority of fathers work as private workers, with unhealthy housing conditions. Characteristics of toddlers are five toddlers born with LBW, one born prematurely. Down syndrome, have a history of severe icterus, nutritional disturbances, persistent diarrhea, children completing Tuberculosis treatment, a history of epilepsy, and the other with a fever cold cough. Our Conclusions: other causes of developmental delays are due to malnourished toddlers being susceptible to disease, and low birth weight.